ENGINERING HOPPER DRYER BUFFER TOOL AT THE PLASTIC WORKSHOP OF POLYTECHNIC ATK YOGYAKARTA - Muhammad Ikhwan; Diana Yuliastuti (Berkala Penelitian Teknologi Kulit, Sepatu, dan Produk Kulit, 2024)
Plastic Laboratory is one of laboratory at ATK Polytechnic Yogyakarta. Plastic Workshop has several machines including hopper dryer machines that cannot be functioned because of the absence of supporting devices. The design of this hopper dryer support device aims to help the process of operating the hopper dryer that has been in the plastic workshop. This buffer tool is designed according to needs by taking into account the ergonomic value of the machine and plastic workshop room. The design of the Hopper Dryer buffer consists of a Hopper Dryer holder table and a plastic ore transport funnel. In this study, in order to achieve the results of the hopper dryer support device design as expected, several stages or design steps were prepared starting from determining the list of needs, determining concepts, designing components, making detailed technical drawings, materials used, making products and trials. From the analysis of the use of the hopper dryer buffer tool made, it can be concluded that with this buffer device, the hopper dryer that initially could not be functioned can finally be operated properly so that it can help the drying process of plastic ore to be processed on the Blow Molding machine. From the trials carried out with the maximum load, the hopper dryer capacity is safe to use so that if each production process only uses 1/4 of the maximum capacity, the resulting load voltage of 1029 N is still very safe to use.